Motivation, work performance and job satisfaction of public school teachers in Iloilo City - Delgado, Alvin; Fajardo, Ma. Febe; Marzoña, John Patrick; Montaño, Pearly Rose P.; Reyna, Raphy Jho
The study focuses on motivation, work performance and job satisfaction among public school teachers in Iloilo City ; identifies the efforts made by the school and DepEd in motivating public school teachers in order to increase performance and also to determine factors relating to motivation that affects work performance and job satisfaction ; and, recommends appropriate actions the motivation, work performance and job satisfaction of public school teachers. A total of eighty (80) respondents were selected randomly among the four public schools situated within Iloilo City. The schools selected are Iloilo Central Elementary School, Iloilo City High School, Lapaz I Elementary School and Iloilo National High School. Questions about motivation, work performance and job satisfaction were used as analysis through the help of descriptive statistical method. Analysis of the respondents through survey questionnaires reveals that there is a significant efforts being applied by schools and the DepEd in increasing the performance of public school teachers, these efforts takes the form of seminars, trainings, incentives, salary increase, awards and recognition ; salary increase being the most often used by the DepEd. The study also reveals that public school teachers are comfortable with their profession that they have no fear of it losing importance in the future. Most of the teachers also have indicated that they are competent and effective in their profession. The study recommends that the government and school administration to not only continue their efforts but also to continuously improve the techniques and schemes, the government should also find ways to improve the salary level of public school teachers to not only retain public school teachers to not only retain public school teachers but also to attract potential teachers, the study also recommends for the school which is a big factor in increasing work performance by teachers.